2017
DOI: 10.21475/ajcs.17.11.11.pne484
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of grain yield associated characters in Brazilians wheat genotypes (Triticum aestivum L.)

Abstract: The aim of this study was to evaluate the phenotypic interrelation among agronomic characters associated with wheat grain yield of the main Brazilian cultivated genotypes through path analysis in two environments. The tests were conducted in Tenente Portela-RS and Braga-RS. The experimental design was randomized blocks arranged in factorial scheme, 2 locations × 17 genotypes and 3 repetitions. The evaluated characters were plant height, main stem spike mass, tiller spikes mass, main stem spike grains number, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Kavalco et al (2014), obtained results similar to present work. Carvalho et al (2017) reveled direct effect of main stem spike grain mass on grain yield. However, Okuyama et al (2004) reported positive direct effect of high magnitude for genetic correlation, but with low and negative total correlation.…”
Section: Resultsmentioning
confidence: 96%
“…Kavalco et al (2014), obtained results similar to present work. Carvalho et al (2017) reveled direct effect of main stem spike grain mass on grain yield. However, Okuyama et al (2004) reported positive direct effect of high magnitude for genetic correlation, but with low and negative total correlation.…”
Section: Resultsmentioning
confidence: 96%
“…However, the knowledge of yield components with the greatest contribution for seed production should not be based only on simple linear correlation, since its interpretation might lead to errors or misunderstandings, compromising the success of selection (Cruz et al, 2014). In this way, understanding linear correlations between traits allows only identifying tendencies, but it does not formulate cause and effect relationships (Carvalho et al, 2017). Due to this fact, multiple regressions (Stepwise) are used to determine which traits are essential to the dependent trait (Balbinot et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Determining effects are attributed to precipitation and air temperature . Production behavior is dependent on climatic variables, relationships between the characters of interest, and characteristics of the genotypes (Cruz et al, 2014;Carvalho et al, 2017;Szareski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%